2021
DOI: 10.1007/s10961-021-09904-y
|View full text |Cite
|
Sign up to set email alerts
|

Venture creation patterns in academic entrepreneurship: the role of founder motivations

Abstract: The path to academic entrepreneurship is characterized by a sequence of venture creation activities, which can be classified into operational-, financing- and commercialization activities. Academic entrepreneurship research is concerned with the question how different motives of scientists affect the patterns of these venture creation activities. Using a longitudinal two-period dataset of 165 academic entrepreneurs from 73 universities in Germany, we propose and test a multi-activity-based model that links dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 162 publications
(307 reference statements)
1
3
1
Order By: Relevance
“…In total, we received 156 questionnaires that were completed in full or in part. This resulted in a response rate of approximately 14%, consistent with comparable recent studies (e.g., Abbate et al, 2021 ; Hossinger et al, 2021 ; Ng et al, 2020 ). The absolute response rate level may not be high when compared to meta-analytic results obtained by Baruch ( 1999 ) and Pielsticker and Hiebl ( 2020 ).…”
Section: Methodssupporting
confidence: 90%
“…In total, we received 156 questionnaires that were completed in full or in part. This resulted in a response rate of approximately 14%, consistent with comparable recent studies (e.g., Abbate et al, 2021 ; Hossinger et al, 2021 ; Ng et al, 2020 ). The absolute response rate level may not be high when compared to meta-analytic results obtained by Baruch ( 1999 ) and Pielsticker and Hiebl ( 2020 ).…”
Section: Methodssupporting
confidence: 90%
“…A longitudinal study that was carried out in German higher education institutions revealed that self-realization, necessity and desire to improve financial income has increased the likelihood of academics to pursue entrepreneurial initiatives (98). However, this study did not find a significant effect regarding the desire to translate ideas into practice as a strong motivating factor.…”
Section: Societal and Financial Motivations To Pursue Entrepreneurial...contrasting
confidence: 71%
“…Scientists who have a focus on applied research generate results that are closer to application and therefore commercialization (Leitner et al, 2021). The overall aim of generating knowledge that is close to application makes them aware of potential ways to commercialize it, especially via spin-off creation (Hossinger et al, 2021). The idea to bring its own research to the market and having entrepreneurial aspirations can influence the choice of the spin-off channel.…”
Section: Hypothesis 4bmentioning
confidence: 99%